1981
DOI: 10.2307/1589824
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Crude Polysaccharide Extracted from Two Different Immunotype Strains of Hemophilus gallinarum in Chickens

Abstract: Biological activities in chickens of crude polysaccharide extracted from two different immunotype strains of Hemophilus gallinarum (HG), strain 221 and S1, were studied to clarify a type-specific protecting antigen and a toxin. Crude polysaccharide materials extracted from strains 221 and S1 were not only protective but toxic to chickens. They also contained at least two heat-labile antigens. When the polysaccharide materials were subjected to gel filtration on Sepharose 6B by tracing at 280 and 490 nm, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1981
1981
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Crude polysaccharide including typespecific antigen was extracted from H. paragallinarum strain S1, serotype C, and strain 221, serotype A, according to the method of Iritani et al (7). Briefly, 24-hr-old cultured H. paragallinarum cells in chicken meat infusion broth were disrupted with a cell press, and absolute ethanol was added to the supernatant to remove the nucleic acids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude polysaccharide including typespecific antigen was extracted from H. paragallinarum strain S1, serotype C, and strain 221, serotype A, according to the method of Iritani et al (7). Briefly, 24-hr-old cultured H. paragallinarum cells in chicken meat infusion broth were disrupted with a cell press, and absolute ethanol was added to the supernatant to remove the nucleic acids.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in this laboratory, crude polysaccharide antigens were extracted from H. paragallinarum serotypes A and C (7). The polysaccharides were found to contain type-specific antigens.…”
Section: Introductionmentioning
confidence: 99%
“…The LPS of H. paragallinarum has been shown to be lethal for embryonated chicken eggs and to be positive ir a pyrogen test (Konno and Nakase, 1977). Iritani et al (1981) have also shown that a crudely purified polysaccharide extract contains a component that is toxic and causes hydropericardium following intravenous inoculation into chickens. Any records of adverse side reactions will be noted with the various adjuvant systems described below.…”
Section: Adjuvantsmentioning
confidence: 99%
“…Sawata et al (1979) suggested that the capsule of H. paragallinarum contains protective antigens. A crude polysaccharide has also been reported to provide protection that is limited to the Page serovar on which the vaccine is based (Iritani et al, 1981).…”
Section: Protective Antigensmentioning
confidence: 99%
See 1 more Smart Citation